Culture Medium and Varietal Selection for Establishment of Callus Culture of Artemisia annua - Keong, Chin Chee; Nordin, Farah Alia; Bhatt, Arvind; Keng, Chan Lai (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
Plant tissue culture technology offers the potential of producing medicinally important secondary metabolites such as anti-malarial artemisinin from Artemisia annua. In this study, callus induction of three different varieties of A.annua, namely T1, T2 and Hi varieties was carried out using leaf explants on Murashige & Skoog (MS) and Litvay (LV) media with three different supplementations. MS medium added with 0.5 mg/L BA, 0.5 mg/L NAA and 0.5 g/L of casein hydrolysate (CH) induced the highest yield of callus biomass compared to the effect of picloram- or 2,4-enriched MS medium. T2 variety was found to be the highest yielding variety in this medium. Picloram-enriched MS medium induced better callus in term of callus biomass and friability than 2,4-enriched medium. Hi variety induced in MS medium added with 0.5 mg/L picloram produced highest callus biomass among the three varieties. Callus formed on 0.5 mg/L picloram was also much more easily dispersed than callus of all three varieties cultured in the other two MS medium. LV-based medium was generally shown to be poor in inducing callogenic response from leaf explants. Therefore Hi callus sourced from MS medium supplemented with 0.5 mg/L picloram was selected to initiate liquid cell culture of A. annua which can further be explored for production of artemisinin, an anti-malarial compound.Abbreviations: MS – Murashige and Skoog’s salts and vitamins [1]; LV – Litvay medium [2]; BA – 6- benzyladenine; NAA – alpha-napthaleneacetic acid; 2,4-D – 2,4-dichlorophenoxyacetic acid; picloram – 4-amino-3,5,6-trichloropicolinic acid, CH – casein hydrolysate